Hajib bin Zarara Al-Tamimi and his intellectual contributions before Islam - Abdelhadi, Barka Abdoulaye; Adam, Ousmane Mahamat; Chouibou, Mouhamadou (Journal of Arabic Language Sciences and Literature, 2023)
This study deals with the role of Hajib bin Zarara Al-Tamimi, and his intellectual contributions to the pre-Islamic Arab society. Where he had an active presence in the movement of society, and had many contributions in various fields, and social and literary activities, most notably 1 Al-Hakam: Hajib is considered one of the famous rulers, chiefs, and figures, the most valuable of the Arabs in redemption, and the first ruler to rule over himself. That is when they disagreed about his captivity, they asked him to acknowledge the one who captured him, and he also requested that they rule him in himself, so he made a thousand and a hundred camels as a ransom for him from captivity. 2 - Public Speaking: It is a verbal prose hadith that aims to provoke people's feelings and ignite their emotions with a desire to get what they want. It is a power that involves persuading people as much as possible through the presence of the speaker in front of the audience. The preacher had a great position in that period for his ability to defend his people, and Hajib bin Zarara was worthy of that, when he gave his famous sermon in front of Khosrau, he persuaded him to allow his people to go down in the countryside of Iraq when he prevented them from doing so. 3- Arch of the visor: The arch of the visor is one of the important matters in the history of the Arabs in the pre-Islamic era, as its moral value is not equivalent to its value in that era, because he pawned it at Khosrau, in return for his people descending into the countryside of Iraq. This bow, which accompanies him in his travels, was one of his most precious possessions. Because Hajib knows that the lesson is not in the price of the mortgage, because Khosrau does not need what Hajib has. But the lesson in the value of the arc at the usher himself.
Keywords: Hajib bin Zarara; his intellectual contributions; Before Islam